Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

A Theory of Change for Teachers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Ahmed, Shakil; Kaye, Tom; Zubairi, Asma (EdTech Hub, 2022)
The second of a trilogy of Theories of Change (TOCs) that focuses on teachers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how teachers’ professional learning experiences will enable them to support learners in ways that take advantage of available technology. The TOC is a useful tool to support the design, implementation, and evaluation of all programmes and initiatives that are designed for teachers, and aim to improve educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; teachers' professional development; education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6400980 10.53832/edtechhub.0086 10.53832/edtechhub.0088 2405685:29Z2JFJT 2405685:CB5GGAXU
Keywords: _r:AddedByZotZen

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5652015 KerkoCite.ItemAlsoKnownAs: 10.5281/edtechhub.0044 10.5281/zenodo.4610089 10.53832/edtechhub.0044 2339240:D4Q4RX94 2339240:YKVDDCEI 2405685:2T7DPIBU 2405685:BUHD2X9T 2405685:E4I95IWF 2405685:NP95DHA2 2405685:Q2MS5ZSE 2405685:ZSEHKGUN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7054334 ZenodoArchiveConcept: 7054333 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7054334 10.53832/edtechhub.0126 2405685:GQSKFD62 2405685:XLXRPW3Z
Keywords: _r:AddedByZotZen

Parenting in Bangladesh: A Review of the Literature from 2006 to 2018 - Jasmine, Umme Habiba; Nduna, Mzikazi (Journal of Comparative Family Studies, 2022)
This study was a point of departure for future research on the need for a coherent understanding and knowledge of parenting in Bangladesh. This article presents the findings from an integrative research review on parenting in Bangladesh. A comprehensive search conducted in PubMed, Science Direct, and PsychINFO using the keywords “parenting”, “childcare”, “motherhood”, “fatherhood”, “mothering”, “fathering”, each paired with “Bangladesh” yielded 246 articles. Twenty papers published between 2006 and 2018 were selected for thematic analysis based on pre-set criteria. In most studies, the term mother was used interchangeably with parent, with mothers regarded as the primary caregiver. Parenting in the Bangladeshi context was found to be conceptualized primarily in terms of attitudes, disciplinary practices, feeding, parent–child interaction, and psychosocial stimulation. Parenting components aimed at moral development and attachment building in children were underrepresented. The data revealed largely inconsistent and uncoordinated discussions of parental practices, demonstrating the lack of a holistic approach in the literature in Bangladesh. Research on parenting in Bangladesh favors gendered assumptions of females as the primary caregiver. Based on their findings, the authors recommend qualitative studies to better reflect and conceptualize the concept of parenting in Bangladesh.
Publisher: University of Toronto Press KerkoCite.ItemAlsoKnownAs: 10.3138/jcfs-2021-0071 2339240:9PP366GD 2405685:WCUZM8QA
Keywords: Bangladesh; gendered role; integrative review; literature review; mother; mère; parentalité; parenting; revue de littérature; revue intégrée; rôle genré

E-Learning in Bangladesh: A Study of Teachers’ Behavioral Orientation and Affective Alignment in the Post-New Normal - Shamim Miah, A.S.M; Rasel Kabir, Md; Sultana, Sarmin (Contemporary Research in Education and English Language Teaching, 2020)
This study explores the teachers’ behavioral and affective orientation to e-learning that is in practice at all the levels of education in Bangladesh i.e. primary school, secondary school, higher secondary school, college, and university. By investigating the reasons for such disarray, it proposes solutions to overcome them. It acquired its data through online surveys followed by quantitative analysis through descriptive inferential analogies of the logarithmically represented findings. The result of the study documents that teachers’ preparation, technological know-how and adaptation to the e-learning platforms, their methods of teaching, measurement of outcomes, and mapping of curricula suggest that e-learning in Bangladesh is vitiated due to the diffusion in the teaching staff demographics and diluted apprehension of the e-learning. The paper’s primary findings show that Bangladesh’s progress from Education 1.0 to Education 3.0 is more affective and behavioral than cognitive in the implementation; wherein, the very concept of e-learning is diluted or spun around the idea of education via some usage of technology only, more specifically web conference applications which is indicative of Education 2.0 practices. There is no distinction made that separates online learning from e-learning, e-learning from distance and distance from blended learning, etc. in the current environment.
KerkoCite.ItemAlsoKnownAs: 10.33094/26410230.2020.21.16.35 10/gj37h5 2339240:A7RYDPHH 2405685:KVRAQU2P

Integrating ICT in English Language Teaching in Bangladesh: Teachers’ Perceptions and Challenges - Khan, Nafis Mahmud; Kuddus, Khushboo; Kuddus, Khushboo; School of Humanities (English), KIIT Deemed to be University, Bhubaneswar, Odisha, India. (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2020)
The integration of Information and Communication Technology (ICT) in Education especially, in English Language Teaching (ELT) in secondary schools of Bangladesh has been existing for a decade now. However, the status of actual implementation is quite different from the adoption and initiatives taken to integrate ICT in ELT. Therefore, the study aims to investigate the secondary level English language teachers’ attitude towards integration of ICT in Communicative Language Teaching (CLT) and the factors inhibiting the use of it. Further, the paper attempts to examine the challenges faced by the secondary level English teachers of Bangladesh in using ICT in language teaching effectively. In an attempt to examine the attitude of teachers in using ICT in ELT, a quantitative research is designed with a close ended questionnaire to collect the data from a sample of 100 secondary English language teachers of various schools of Bangladesh. The data of the responses is quantified and is analyzed by SPSS 20 program. The obtained data from the questionnaire is examined in order to investigate the perceptions of the secondary level English language teachers towards ICT integrated language teaching and the challenges of the implementation of ICT in ELT. In conclusion, the outcome of the research would provide significant information about the attitude of the teachers towards ICT integration in ELT and the challenges faced by them and hence, the study would help the policy makers and the teachers to enhance the effectiveness of using ICT in ELT.
KerkoCite.ItemAlsoKnownAs: 10.21659/rupkatha.v12n5.rioc1s23n1 10/gj37jk 2339240:C45NVN5G 2405685:7JJTNDXM

Compendium of Social Protection Research in Bangladesh - Government of Bangladesh (The General Economics Division (GED), Bangladesh Planning Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:L7AXVDVM 2405685:CJY2YG6P 4803016:G647E99W

How Bangladesh repurposed pre-existing online platforms to reimagine education during Covid-19 - Bangladesh), Anir Choudhury (a2i (EdTech Hub, 2021)
Forty-two million. That is the total number of students in Bangladesh. Forty-two million potential leaders of tomorrow. Forty-two million reasons to be hopeful for the country’s future. Forty-two million students who, because of Covid-19, were left without classrooms, without their friends, without their schools and colleges – without formal education.
KerkoCite.ItemAlsoKnownAs: 2405685:HVNU4INN 2405685:TA8WC382
Keywords: _EdTechHub_Output

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Secondary Education During Lockdown Situation Due to Covid-19 Pandemic in Bangladesh: Teachers’ Response on Online Classes - Farhana, Z; Tanni, S; Shabnam, S; Chowdhury, S (Journal of Education and Practice, 2020)
Online classes started in many secondary schools one month after the compulsory closure of all education institutions in Bangladesh. This study explores the current scenario as well as challenges of adaptation of online classes in secondary education in terms of teachers’ experience. The study followed sequential exploratory mixed-method approach. Five secondary teachers were interviewed and 54 secondary teachers from 17 districts in Bangladesh were surveyed over telephone, Google forms and by email. The quantitative data was analyzed with Microsoft Excel and the thematic analysis approach had been followed for the qualitative one. The findings revealed that a good number of teachers have started teaching online by using social media platforms despite of not having any training or experience. Very few respondent teachers were found to take online examination; instead they are trying to assess the students from the feedback of given home works and home assignments. Teachers are facing numerous challenges like deficit of digital equipment, lack of expertise, unfamiliarity with the LMS, proficiency in assessment technique etc. The paper concludes with few recommendations such as providing proper devices to the teachers and students to participate in online class; facilitate rigorous training to enhance technology-based skills and capacities of the teachers so as to get the expected outcome.
KerkoCite.ItemAlsoKnownAs: 10.7176/jep/11-20-11 10/gj37h6 2339240:L9JH4WCG 2405685:3E5UXJXJ

TV-Based Learning in Bangladesh: Is it Reaching Students? - Biswas, Kumar; Asaduzzaman, T.M.; Evans, David; Fehrler, Sebastian; Ramachandran, Deepika; Sabarwal, Shwetlana (World Bank, 2020)
Is TV-based learning during COVID-19 school closures in Bangladesh reaching students? Most students (86 percent) within our sample of more than 2,000 Grade 9 stipend recipients are aware of government provided TV-based learning programs; yet only half of the students with access to these programs choose to access them. Also, very few students (21 percent) have access to government provided online learning programs, and among those that do, only about 2 percent choose to access them. There is a perceptible decline in the time students spend studying at home after school closures. This may be linked to the fact that 1 in 2 parents claim they are unable to help their children with new topics. Despite lower education, mothers are significantly more likely to be involved in the child’s education compared to fathers. Most students (90 percent) claim they have a supportive environment at home for studying. This is true for both boys and girls. Finally, nearly 65 percent of households in our sample report declines in income and 28 percent had to decrease the amount of food consumed within the household in the previous week.
KerkoCite.ItemAlsoKnownAs: 10.1596/34138 2339240:C5IHCNQD 2339240:IM47JZ2Z 2339240:M56ICKNT 2339240:SVXNVHB3 2405685:2NGQ3V9V 2405685:5SKQVXG9 2405685:F8Y2BXPY 2405685:HCD7DA27 2405685:XQXHTGSI 2534379:EBH9X23R
Keywords: Access to Education; Distance Learning; Education; Online Learning; School Closure; Secondary Education; ___working_potential_duplicate

Making Vision 2041 a Reality: Perspective Plan of Bangladesh 2021-2041 - General Economics Division, Bangladesh Planning Commission, Ministry of Planning, Government of the People’s Republic of Bangladesh (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Z8H6NIQ8 2405685:KJM92W3X

Digital in Bangladesh: All the Statistics You Need in 2021 - DataReportal (DataReportal – Global Digital Insights, 2021)
Our huge new collection of statistics and insights into how people in Bangladesh use the internet, social media, mobile, and ecommerce in 2021.
KerkoCite.ItemAlsoKnownAs: 2339240:I94ZZMY6 2339240:J4Q9N36L 2405685:3U3S5NRZ 2405685:G7IWS6TF 2405685:YVMDGILY 2534379:969KQJR3
Keywords: ___working_potential_duplicate

Five lessons learnt from Bangladesh's experience responding to COVID-19 - Sarwar, Mohammad Afzal Hossain,; Hossain, Iqbal; Kaye, Tom (EdTech Hub, 2020)
by Md. Afzal Hossain Sarwar (a2i), Iqbal Hossain (UNICEF Bangladesh) and Tom Kaye (EdTech Hub) In recent months, the EdTech Hub has produced a range of documents to support and guide countries as they develop and implement plans to help students keep learning during school closures. Some of the work we have produced includes: a guide to a five-part response…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707856 10.5281/zenodo.4707858 2339240:3JLSUFML 2339240:PISQI3AG 2405685:7G3XE8J6 2405685:HXB42AHC 2405685:PH8ICW77 2405685:RDMBW97E
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7591685 ZenodoArchiveConcept: 7591684 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7591685 10.53832/edtechhub.0146 2405685:J8IB7LVG 2405685:V4EVQ39I
Keywords: _r:AddedByZotZen

Bangladesh - Overview - World Bank (World Bank, 2021)
The International Development Association (IDA) has supported Bangladesh since 1972, just after the country’s independence. Since then, the World Bank through its concessional lending arm has committed nearly $26 billion in grants and interest-free credits to Bangladesh.
KerkoCite.ItemAlsoKnownAs: 2339240:9GAMGSVG 2405685:RUP3LCB2

Challenges and Developments in the Higher Education System of Bangladesh: Keys to Way Forward - Chowdhury, Mahfuzul Hoque; Absar, Mir Mohammed Nurul; Quader, Syed Manzur (Handbook of Education Systems in South Asia, 2020)
Series Title: Global Education Systems KerkoCite.ItemAlsoKnownAs: 10.1007/978-981-13-3309-5_57-1 2339240:GB9KNSCS 2405685:WA9WN3R2

Bangladesh - World Inequality Database (WID - World Inequality Database, 2021)
Bangladesh The source for global inequality data. Open access, high quality wealth and income inequality data developed by an international academic consortium.
KerkoCite.ItemAlsoKnownAs: 2339240:QDDJSFXN 2405685:NF7Q3FVW

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6942540 10.53832/edtechhub.0103 2405685:77665EVG 2405685:JV4F45P5
Keywords: _r:AddedByZotZen

COVID-19 and Bangladesh: challenges and how to address them - Anwar, Saeed; Nasrullah, Mohammad; Hosen, Mohammad Jakir (Frontiers in Public Health, 2020)
As the coronavirus outbreak quickly surges worldwide, many countries are adopting non-therapeutic preventive measures, which include travel bans, remote office activities, country lockdown, and most importantly, social distancing. However, these measures face challenges in Bangladesh, a lower-middle-income economy with one of the world's densest populations. Social distancing is difficult in many areas of the country, and with the minimal resources the country has, it would be extremely challenging to implement the mitigation measures. Mobile sanitization facilities and temporary quarantine sites and healthcare facilities could help mitigate the impact of the pandemic at a local level. A prompt, supportive, and empathic collaboration between the Government, citizens, and health experts, along with international assistance, can enable the country to minimize the impact of the pandemic.
KerkoCite.ItemAlsoKnownAs: 10.3389/fpubh.2020.00154 2339240:Q8J6VE8P 2405685:6JBHGPXJ

Students perception of mobile learning during COVID-19 in Bangladesh: university student perspective - Biswas, Bikram; Roy, Sajib Kumar; Roy, Falguni (Aquademia, 2020)
The aim of this study is to measures the student’s perception of using mobile for learning during COVID-19 in Bangladesh especially at the university student’s perspective. During the COVID-19 pandemic period, mobile learning may help the students to fulfill the study gap. Due to COVID-19 pandemic 213 countries, higher education has affected all over the world of June 2020. Although all of the developed countries considered mobile learning as an effective tool for education, it is not used properly in Bangladesh. This survey method conducted on 416 students from different university students in Bangladesh to understand the student’s perception of using mobile phones as a learning system. The findings of this study show that most of the students at the university level have a positive perception of m-learning. This study revealed that m-learning is very helpful to recover the study gap during this COVID-19 pandemic time and the findings of this study will help the education policymaker as well as the educational institutions to incorporate mobile learning technology for the whole system where social media may enhance the process of teaching and learning.
Publisher: Veritas Publications LTD KerkoCite.ItemAlsoKnownAs: 10.29333/aquademia/8443 2339240:KHZM9M89 2405685:RBZUY224

Bangladesh Population (2021) - Worldometer (2021)
Population of Bangladesh: current, historical, and projected population, growth rate, immigration, median age, total fertility rate (TFR), population density, urbanization, urban population, country's share of world population, and global rank. Data tables, maps, charts, and live population clock
KerkoCite.ItemAlsoKnownAs: 2339240:6KUWCRCQ 2405685:2LS69KMG

Investigating the mediating role of online learning motivation in the COVID-19 pandemic situation in Bangladesh - Rahman, Md. H Asibur; Uddin, Mohammad Shahab; Dey, Anamika (Journal of Computer Assisted Learning, 2021)
The purpose of this paper is to investigate the mediating role of online learning motivation (OLM) in the COVID-19 pandemic situation in Bangladesh by observing and comparing direct lectures (DL), instructor–learner interaction (ILI), learner–learner interaction (LLI), and internet self-efficacy (ISE) as predictors of OLM and online learning satisfaction (OLS). Data were collected from 442 undergraduate and graduate students from more than 35 universities in Bangladesh. To test the hypotheses, the PLS-SEM approach was applied using SmartPLS 3.0. The study shows a significant mediating role of OLM between the independent variables and learning satisfaction. In addition, DL, ILI, and ISE are shown to be significant predictors of student satisfaction. The findings have a number of valuable implications for education policy makers, universities, instructors, and students. Moreover, the study suggests some new research perspectives to overcome the limitations of this research and to gain precise knowledge on students' learning motivation and satisfaction regarding other online classes for different categories of students (e.g., high school and college, professional, and PhD).
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/jcal.12535 KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12535 2339240:D2LCXIHU 2405685:DUEDNPFM
Keywords: Bangladesh; COVID-19; interactions; learning motivation; learning satisfaction; online education

An interactive math braille learning application to assist blind students in Bangladesh - Nahar, L; Sulaiman, R; Jafaar, A (Assistive Technology, 2020)
Due to the lack of affordable assistive tools for learning mathematics, blind students in Bangladesh still use outdated learning tools like Tailor Frame. Therefore, demand for a low-cost technological tool is there that will help the blind students to learn math braille and calculate numbers more easily. To provide an effective and affordable assistive tool, this study begins with a needs assessment study to identify the basic needs of blind students in learning math braille and solving mathematical calculations. Afterward, a mobile phone based interactive assistive application is proposed to improve the learning facilities of math braille using Nemeth code for blind students in Bangladesh. Interfaces of the application are designed based on their needs. Besides, interaction methods (such as, hearing & touching) of blind students with the physical world were another criterion in designing very interactive interfaces that provide self-learning facilities. The interfaces are evaluated by the teachers, experts, and end users in order to identify the usability. The evaluation shows a promising result toward the acceptability of the designed application. Therefore, this application can be helpful for the blind students to learn math braille using Nemeth Code.
KerkoCite.ItemAlsoKnownAs: 10.1080/10400435.2020.1734112 10/gkm64j 2339240:9H367DU5 2405685:9SMEBFMC

Adolescence in the Time of Covid-19: Evidence from Bangladesh - Baird, Sarah; Seager, Jennifer; Sabarwal, Shwetlena; Guglielmi, Silvia; Sultan, Maheen (2020)
This note examines the effects of COVID-19 and subsequent economic and educational disruptions on adolescent well-being in Bangladesh. The analysis is based on data from 2,095 in-school adolescents aged 10–18 collected preCOVID-19 (February–March 2020) through a field survey for an ongoing impact evaluation, and a follow-up virtual survey undertaken early in the pandemic (May–June 2020). Findings show large household-level economic impacts associated with increased food insecurity, anxiety, and mental health issues among adolescents. In addition, school closures have decreased adolescents’ access to learning, increased time spent on household chores, and affected future job aspirations. The impacts are particularly large for girls and for adolescents from more vulnerable households. Policy makers need to consider policies that facilitate school return, targeting girls and the most vulnerable. They also need creative school-based programming to address the likely long-run physical and mental health effects of COVID-19 on young people.
KerkoCite.ItemAlsoKnownAs: 2339240:VBAB3NLH 2405685:4FAR45UM

Early effects of the COVID-19 lockdown on children in rural Bangladesh - Makino, Momoe; Shonchoy, Abu S; Wahhaj, Zaki (2021)
Using data collected through a telephone-based survey in rural Bangladesh during the height of the pandemic, we present evidence on the eﬀects of COVID-19-led lockdown and school closures on children, focusing on three child-related outcomes: time use of children during the school closure, plans regarding children’s schooling continuation, and the incidence of child marriages. Our analysis reveals heterogeneity in the eﬀects of lockdown and school closure in terms of the child’s gender and the type of shocks. We ﬁnd a decrease in children’s study time and an increase in time spent on household chores during the school closure, and these changes were signiﬁcantly larger for girls than for boys. Within the household, respiratory illness lowered expectations that a child would return to school and increased the probability of marriage-related discussions for girls. Our ﬁndings oﬀer a cautionary tale regarding the potential longterm eﬀects of pandemic for girls in developing countries.
KerkoCite.ItemAlsoKnownAs: 2339240:EHS3BXYL 2405685:HBIVSCZT
Keywords: ⛔ No DOI found

COVID-19 Response and Recovery Plan - Government of Bangladesh (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:LEYGY974 2405685:6W2B7V7U

Making Vision 2041 a Reality: Perspective plan of Bangladesh 2021-2041 - Ministry of Planning (Ministry of Planning,Government of the People’s Republic of Bangladesh, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PCSGGS87 2405685:T9BWKY5Z

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651981 previousDOI: 10.5281/zenodo.5109678 previousDOI: 10.5281/zenodo.4943272 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4943272 10.5281/zenodo.5109678 10.5281/zenodo.5651981 2339240:TCHKGQZS 2405685:QUJHNPRD 2405685:XH44AG5R 2405685:YULPZE4D
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

A simulation of COVID-19 school closure impact on student learning in Bangladesh - Rahman, Tashmina; Sharma, Uttam; World Bank (World Bank, 2021)
This Note presents results from a series of simulations that aim to capture the impacts that school closures in Bangladesh might have on the learning levels, enrollment and future earnings of children and students using a methodological tool developed by the Education Global Practice of the World Bank. We find that overall loss in learning for every child enrolled in school even in the most optimistic scenario is expected to be substantial and the economic implications of the learning losses are huge. Available data also indicates that remote learning requires to be made more effective. It is hoped that the insights from this note will be useful for the government, non-government, private sector and civil society engaged in education service delivery as they are attempting to forge effective partnerships during and after the crisis. There is an urgent need to substantially reduce additional dropouts and absenteeism through stipends and safe school opening and communication campaigns.
KerkoCite.ItemAlsoKnownAs: 2339240:WGZJQAIX 2405685:BS37TZAZ
Keywords: Access to Computers; Access to Education; Achievement Gains; Age Differences; At Risk Students; Attendance; Bangladesh; Barriers; COVID-19; Delivery Systems; Disadvantaged Youth; Distance Education; Dropout Prevention; Economic Impact; Elementary Secondary Education; Foreign Countries; Gender Differences; Handheld Devices; Income; Pandemics; Partnerships in Education; Program Effectiveness; Radio; Remedial Instruction; Rural Urban Differences; School Closing; Simulation; Telecommunications; Television

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

Impact of COVID-19 on the institutional education system and its associated students in Bangladesh - Emon, Efta Khairul Haque; Alif, Ashrafur Rahman; Islam, M. Shahanul (Asian Journal of Education and Social Studies, 2020)
KerkoCite.ItemAlsoKnownAs: 10.9734/ajess/2020/v11i230288 2339240:X4UBFSR8 2405685:P48U5KA8
Keywords: Bangladesh; COVID-19; Coronavirus; education; impact; poverty.

World Bank helps Bangladesh provide education and skills training to poor children and youths - ReliefWeb (OCHA, 2021)
English News and Press Release on Bangladesh about Contributions, Education, Epidemic and more; published on 18 Jan 2021 by World Bank
KerkoCite.ItemAlsoKnownAs: 2339240:YW8V8Z46 2405685:BLFQEDDB

Focus country: Bangladesh - EdTech Hub (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:R62Y25DW 2405685:IFIR3QC9

Bangladesh Education Sector Analysis - GPE (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PU356S5T 2405685:C7TES4HM

Population, total - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HXP4NC9X 2405685:FY2PMI2Y

Population growth (annual %) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:56YJRP9F 2405685:GTPKXNXJ

Secondary education, pupils - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KTBRX27R 2405685:F2U9JVYV

Secondary education, teachers - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:UDK7XP58 2405685:EKHHRCF2

School enrollment, secondary (% net) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2E6RZ789 2405685:V7GDFZV7

Secondary education, pupils (% female) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KPLXFGAC 2405685:LDBMGJIF

Secondary education, teachers, female - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:EB4PD5EG 2405685:LB4ZKJHT

WFP and Government of Bangladesh deliver high-energy biscuits to school children affected by COVID-19 school closures - WFP (ReliefWeb, 2020)
English News and Press Release on Bangladesh about Education, Food and Nutrition and Epidemic; published on 19 May 2020 by WFP
KerkoCite.ItemAlsoKnownAs: 2339240:HZUY9LBT 2405685:9Z9XFPC8

Rural population (% of total population) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:VDAAYFPJ 2405685:3K9WFJ7B

Bangladesh - COVID 19 School Sector Response Project (English) - World Bank (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:KGIQQEBE 2405685:IKNKMG2R

COVID-19 boosts digitization of higher education in Bangladesh - Rahman, M; ul-Aziz, M; Ahmed, S (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:YMV5DY38 2405685:F66HV332

Population ages 15-64 (% of total population) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:7R2JJF4R 2405685:5NXMIQQ7

Keeping Bangladesh’s Students Learning During the COVID-19 Pandemic - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ARRPM4JP 2405685:B9E9UBBB

Coronavirus Outbreak, Schooling and Learning: Study on Secondary School Students in Bangladesh - Asadullah, N; Bhattacharjee, A; Tasnim, M; Mumtahena, F (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Q68A9V5S 2405685:KEVNB97X

Education sector plan (ESP) for Bangladesh: Fiscal years 2020/21-2024/25 - MoE (Ministry of Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:QEU82LB4 2405685:6AMSJQTC

Mental health and learning: BRAC’s response in Bangladesh during Covid-19 - Ahmad, J; Mariam, E; Sadaf, B; Sarwar, S; Siddique, S; Zaman, S (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:NT98ND5A 2405685:S58SFAFK

Summative Evaluation of GPE’s Country-Level Support to Education: Bangladesh - GPE (Global Partnership for Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:VBSUZLDH 2405685:EHB63PAS

Human Development Report 2020: The Next Frontier - Human Development and the Anthropocene. Bangladesh. - United Nations Development Programme (United Nations, 2020)
KerkoCite.ItemAlsoKnownAs: 10.18356/9789210055161 2339240:ZBYSBI9Y 2405685:225TWATP
Keywords: ___working_potential_duplicate

Assessment of Distance Learning Initiative of the Government of Bangladesh during COVID-19 Pandemic - Das, H (a2i, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:QP4P29MJ 2405685:BV6K34UF

Take-up, Use, and Effectiveness of Remote Learning Technologies in Bangladesh during COVID-19 - Beam, E; Mukherjee, P; Navarro-Sola, L (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:2BEQ3IEH 2405685:PW8FDPUE

How BRAC is supporting Bangladesh to continue education in a pandemic - Chowdhury, Zaian; Islam, Rubab; Saltmarsh, Sarah-Jane (2020)
Library Catalog: blog.brac.net Section: Learning KerkoCite.ItemAlsoKnownAs: 2339240:62DZHUDL 2339240:YPXY5VS5 2405685:8CMZMYMX 2405685:JGHI5FAV
Keywords: ___working_potential_duplicate

Conditional Cash Transfer, Loss Framing, and SMS Nudges: Evidence from a Randomized Field Experiment in Bangladesh - Fujii, Tomoki; Ho, Christine; Ray, Rohan; Shonchoy, Abu (2021)
Conditional cash transfers (CCTs) have become one of the most common policy interventions to increase school attendance, but the cost-eﬀectiveness of such interventions has not attracted the attention it deserves. Hence, in addition to a standard CCT implementation, we experimentally study two potential ways to improve the cost-eﬀectiveness of school attendance interventions: (i) SMS information nudges and (ii) loss framing in CCTs. The former provides school attendance information to parents and the latter exploits the endowment eﬀect. Consistent with the existing literature, CCT intervention signiﬁcantly increases school attendance. We also ﬁnd that the loss framing marginally increases attendance over and above the ∗We would like to thank Joseph Altonji, James Berry, Barbara Biasi, Gaurav Dutt, Maulik Jagnani, Costas Meghir, Rohini Pande, Rebecca Thornton, and seminar attendees at Monash and Yale for insightful comments and suggestions. We also thank Akshat Daga, Alekhyo Roychowdhury, Ishaan Malik, and Snehal Modi for research assistance. We beneﬁted from data collection support from MOMODa Foundation and technical support from the Metakave team to automate the process of sending SMS. Finally, we express our sincere gratitude to the participating schools, the students, their parents, and the teachers. Funding from the Shirin Fozdar and Singapore Ministry of Education Academic Research Fund Tier 1 Grant (17-C244-SMU-004) and Japan Center for Economic Research are gratefully acknowledged. This research was approved by the Singapore Management University Institutional Review Board (IRB-16-082-A092-C2(220)). The trial in this study was registered in the AEA RCT registry under AEARCTR-0002373. All mistakes remain ours.
KerkoCite.ItemAlsoKnownAs: 2339240:KUH42MFY 2405685:JG23VUNM
Keywords: ⛔ No DOI found

A Simulation of COVID-19 School Closure Impact on Student Learning in Bangladesh [Book Chapter] - Rahman, Tashmina; Sharma, Uttam (World Bank, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1596/35043 2339240:4MHUSRIF 2405685:RDF4ZFYM

Staying Tuned Radio Programming for Sustained Behaviour Change and Accountability in Cox’s Bazar, Bangladesh - Ergül, H (UNICEF, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:GJPSTJEE 2405685:DUQRTVUY

Population ages 0-14 (% of total population) - Bangladesh | Data - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QGQ9PZAD 2339240:R4T4RZYH 2405685:6VPIRD86 2405685:BS9S34JU

Final Report on: Assessment of Distance Learning Initiative of the Government of Bangladesh during COVID-19 Pandemic - a2i (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Q6R8864R 2405685:3K8CG3MF

Combatting the impact of COVID-19 school closures in Bangladesh - Rahman, Tashmina; Ahmed, Ramim (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:N456FTY7 2405685:27LNFHVR

A Rapid Assessment: Impact of COVID-19 on Education in Bangladesh - BRAC (Advocacy for Social Change (ASC), BRAC, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:8UGKK4SX 2405685:7PRVRPXW

Summative Evaluation of GPE's Country-level Support to Education. Bangladesh - Results for Development (Universalia, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:2UZNK2DF 2405685:JCNQQAWC

Summary: Webinar on COVID-19 fallout on poverty and livelihoods in Bangladesh: results from SANEM’s nation-wide survey conducted in Nov-Dec 2020 - SANEM (SANEM, 2021)
The 10th episode of SANEM Shongzog on "COVID-19 Fallout on Poverty and Livelihoods in Bangladesh: Results from SANEM's Nationwide Survey (Nov-Dec 2020)" was held on 23 January 2021.
KerkoCite.ItemAlsoKnownAs: 2339240:KE7K5Y72 2405685:9MSRWZEF

A rapid assessment: Impact of COVID-19 on Education in Bangladesh - Advocacy for Social Change, BRAC; BRAC Education Programme (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:JEFXQAWR 2405685:B2L94Z4W

A Simulation of COVID-19 School Closure Impact on Student Learning in Bangladesh [Web page] - Rahman, Tashmina; Sharma, Uttam (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KMHYAN74 2405685:5NGZFQW4

TV-Based Learning in Bangladesh: Is it Reaching Students? - World Bank (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:CCPPQ9BH 2405685:KWVCWU5L
Keywords: ___working_potential_duplicate

Audio Lessons Through Radio for Primary Education Set for Launch -With Support from UNESCO CapED Programme for COVID-19 Educational Response for Bangladesh - UNESCO (UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:I7MG6YLA 2405685:Q34TK2MX

A Simulation of COVID-19 School Closure Impact on Student Learning in Bangladesh [Report] - Rahman, Tashmina; Sharma, Uttam (World Bank, 2021)
This Note presents results from a series of simulations that aim to capture the impacts that school closures in Bangladesh might have on the learning levels, enrollment and future earnings of children and students using a methodological tool developed by the Education Global Practice of the World Bank . We find that overall loss in learning for every child enrolled in school even in the most optimistic scenario is expected to be substantial and the economic implications of the learning losses are huge. Available data also indicates that remote learning requires to be made more effective. It is hoped that the insights from this note will be useful for the government, non-government, private sector and civil society engaged in education service delivery as they are attempting to forge effective partnerships during and after the crisis. There is an urgent need to substantially reduce additional dropouts and absenteeism through stipends and safe school opening and communication campaigns.
Accepted: 2021-01-25T16:58:03Z KerkoCite.ItemAlsoKnownAs: 2339240:A2JMJBKU 2405685:TU8UCJ3G
Keywords: Coronavirus; Covid-19; Distance Learning; Education Quality; Pandemic Impact; Primary Education; School Closure; School Dropout; Secondary Education; Student Learning

ঘরে বসেই শিক্ষা - EduHub Bangladesh (LearnFromHome, 2020)
ঘরে বসেই শিক্ষা
KerkoCite.ItemAlsoKnownAs: 2339240:8GSQEBBW 2405685:5FBPQTZ8

EdTech Horizon Scan: Rapid scan of online safety in education - Mazari, Haani; Kaye, Tom (EdTech Hub, 2022)
This EdTech Horizon Scan examines the issue of online safety in digital education — why it should be prioritised, how it is currently being approached, and its potential to become central to education design in low- and middle-income countries. Given that the internet has no borders, there is much to be done to address online safety in all parts of the world — high-income and low- and middle-income countries alike. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7336710 ZenodoArchiveConcept: 7336709 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7336710 10.53832/edtechhub.0136 2339240:4TCBX2GH 2405685:3QBCENK5 2405685:AWHK2L8L
Keywords: _r:AddedByZotZen

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10604329 ZenodoArchiveConcept: 10604328 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080685 10.53832/edtechhub.1005 2405685:GXMUGXHE 2405685:RK44C9BZ
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Parenting and child’s (five years to eighteen years) digital game addiction: A qualitative study in North-Western part of Bangladesh - Keya, Farah Deba; Rahman, Md Mostafizur; Nur, M. Tareq; Pasa, Md Kamal (Computers in Human Behavior Reports, 2020)
Globally, addiction to digital game among the children and adolescents is a growing concern due to its increasing rate of users and adverse effects on their personal including health and social life. Reviewing the literatures shows a number of factors for child’s digital game addiction. Of the literatures, only a few plausibly shows some form of parenting be a cause for digital game addiction, but under what conditions of parenting influence child to be addicted to digital game is not adequately addressed. Aiming to address the gap, a qualitative study was conducted in North-western Bangladesh using Ethnographic Interview with children and Indepth Interview with parents. The data was analyzed manually following thematic framework. The result of the study shows troubled child-parent relationship and parental attitudes for making their child competitive in education, parental neglect, loneliness and anxiety of the child, and permissive parenting are attributed to digital game addiction. Its social basis is emanated from the family’s asymmetrical role in a market based society. Making a child competitive and capable for future market system is over prioritized, whereas providing emotional security is undermined. It also argued that in a capitalistic society, parents has turned tobe a less authoritative figure to deal children’s issue due to the father’s inability to address economic needs of the family adequately and mothers’ economic dependence to their male counter-part. In such a context, parents are compelled to minimize the gap by offering or allowing child to digital game and so gradually children become addicted to digital game. This argument supported the idea of Frankfurt school on how people attracted and depended on culture industry.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.chbr.2020.100031 2339240:EMRM4CEY 2405685:FML9MHFG
Keywords: Digital game addiction; Economic pressure; Emotional security; Parental neglect; Permissive parenting; Troubled child-parent relationship

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

Characteristics of effective teacher education in low- and middle-income countries: an overview (HDR10A) - Haßler, Björn; McBurnie, Chris; Allier-Gagneur, Zoe; Damani, Kalifa (EdTech Hub, 2020)
previousDOI: 10.5281/zenodo.3873458 EdTechHub.Copy: 2129771:2BEHBMUH EdTechHub.Copy: 2129771:2BEHBMUH EdTechHub.Copy: 2129771:C6TREICJ EdTechHub.Copy: 2129771:C6TREICJ EdTechHub.Source: 2405685:HFKVA2IQ EdTechHub.Source: <this> KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3873458 10.53832/edtechhub.0006 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

COVID-19 Response and Recovery Plan - Ministry of Primary and Mass Education (Government of People's Republic of Bangladesh, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:433RGDYT 2339240:6Q5BVEZA 2339240:GJLEVTTL 2405685:52CDSLIM 2405685:8KHDLPVL 2405685:SV9HP48X

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4540204 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4540204 10.5281/zenodo.4540204 2339240:26GYDUTU 2339240:2Q9AWGM3 2339240:IQ36IBT8 2339240:MDUWMNQ5 2339240:P9XQBBQC 2405685:856UY54Y 2405685:CZZ5WHT7 2405685:P9T68ACJ 2405685:UGZDH4LB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

How to re-imagine learning in the wake of Covid-19 (EdTech Hub, 2020)
Last week the EdTech Hub, #NextGenEdu, and Education Development Trust convened experts, policymakers, and implementers to discuss their visions for a reimagined approach to learning in the wake of coronavirus. The invited speakers were: Mohibul Hasan Chowdhury, Deputy Minister of Education, Bangladesh Ministry of Education Jim Ackers, Regional Education Advisor, UNICEF South Asia Regional Office Sonam Wangchuk, Founder, Students’ Educational…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707880 2405685:KDWC5B3N
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

New Brief: Monitoring Distance Learning During the Covid-19 Pandemic - Bashir, Amreen; Groeneveld, Caspar; Kaye, Tom (EdTech Hub, 2020)
In the initial rush to respond to school closures, countries focused on rolling out distance education. Policy-makers now realise that effective distance education requires robust data generated via high-quality monitoring. This blog highlights the findings of a brief synthesising effective practices in monitoring distance education. Since March 2020, the Covid-19 pandemic has impacted 36 million learners in Bangladesh. Schools closed…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4708238 2405685:73G8TGWV
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Lowering Barriers to Remote Education: Experimental Impacts on Parental Responses and Learning - Beam, Emily; Mukherjee, Priya; Navarro-Sola, Laia (2022)
We conduct a randomized controlled trial with households of secondary school students in Bangladesh to investigate how parents adjust their investments in response to three educational interventions: an informational campaign about an educational phone application, an internet data subsidy, and one-on-one phone learning support. We find that offering an educational service in a context where other barriers to take-up exist can still trigger parental educational investments by acting as a signal or nudge. These behavioral changes result in lasting learning gains concentrated among richer households, reflecting that the relevant behavior changeincreased tutoring investmentis easier for them to implement. In contrast, when interventions do increase take-up, they have the potential to narrow the socioeconomic achievement gap. We observe that increased usage of the targeted educational service limits parental behavioral responses. This implies that learning gains in these cases are directly caused by the potential effectiveness of the services adopted. In our setting, remote one-to-one teacher support improves learning among students from poorer households, whereas receiving the free data package jointly with the app information has no impact on learning.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4234910 2339240:VTATZW3D 2405685:T9HU5JTI
Keywords: educational inequality; educational technology; human capital; parental investments

Lowering Barriers to Remote Education: Experimental Impacts on Parental Responses and Learning - Beam, Emily; Mukherjee, Priya; Navarro-Sola, Laia (2022)
We conduct a randomized controlled trial with households of secondary school students in Bangladesh to investigate how parents adjust their investments in response to three educational interventions: an informational campaign about an educational phone application, an internet data subsidy, and one-on-one phone learning support. We find that offering an educational service in a context where other barriers to take-up exist can still trigger parental educational investments by acting as a signal or nudge. These behavioral changes result in lasting learning gains concentrated among richer households, reflecting that the relevant behavior changeincreased tutoring investmentis easier for them to implement. In contrast, when interventions do increase take-up, they have the potential to narrow the socioeconomic achievement gap. We observe that increased usage of the targeted educational service limits parental behavioral responses. This implies that learning gains in these cases are directly caused by the potential effectiveness of the services adopted. In our setting, remote one-to-one teacher support improves learning among students from poorer households, whereas receiving the free data package jointly with the app information has no impact on learning.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4234910 2339240:VTATZW3D 2405685:T9HU5JTI
Keywords: educational inequality; educational technology; human capital; parental investments

Effective Assessment and Progress Monitoring in an Online Environment: A Study in Six Countries - T4 Education; EdTech Hub (EdTech Hub, 2022)
The study was undertaken in six countries – Bangladesh, India, Nigeria, Pakistan, Philippines, and South Africa. The data collection involved focus group discussions with two held in each country..
KerkoCite.ItemAlsoKnownAs: 2339240:PA9TD6UB 2405685:E66UZCLZ

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5602863 10.53832/edtechhub.0063 2339240:I3JETHDB 2405685:5ZF9VGMK 2405685:6P5Q5IRZ 2405685:BIRTYTRC
Keywords: _r:AddedByZotZen

Annual Primary School Census 2019 (Draft) - MoPME; Directorate of Primary Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:HALFYWI8 2405685:LEVHI9LQ

Dearth of research in Bangladeshi universities - Momin, S (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X9NZ9GIQ 2405685:B5DNCPYF

Countries by Density - World Population Review (World Population Review, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QLHYHSIQ 2405685:S4R4KANR

Population by Country - Worldometer (World Population Review, 2021)
List of countries and dependencies in the world ranked by population, from the most populated. Growth rate, median age, fertility rate, area, density, population density, urbanization, urban population, share of world population.
KerkoCite.ItemAlsoKnownAs: 2339240:SI7BVSX4 2405685:A3INEC8H

Recovery of Learning Loss Created Due to COVID-19 Crisis: Analysis of Bangla Learning Outcomes and Identification of Content - NAPE; Room to Read (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:6BFW7CPF 2405685:3WDEFT65

2019 Civil Society Organization Sustainability Index - for Asia 6th Edition – December 2020 - USAID (United States Agency for International Development Bureau for Democracy, Conflict and Humanitarian Assistance Center of Excellence on Democracy, Human Rights and Governance, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:9L542D8M 2405685:2GPSJK4R

UNICEF scales up support to keep children learning, as COVID-19 forces schools to close - UNICEF (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:7R2QCCFC 2405685:A5P8SUV9

Covid-19 disrupts education in rural Bangladesh - Uttom, Stephan; Rozario, Rock (UCA News, 2020)
Pupils and teachers lament lack of access to online classes due to poverty
KerkoCite.ItemAlsoKnownAs: 2339240:Z2PZ4JBN 2405685:P9WN6HSY

Achieving mobile-enabled digital inclusion in Bangladesh - GSMA (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:668LBR98 2405685:W5VR72AL

TV-Based Learning in Bangladesh: Is it Reaching Students? - World Bank (World Bank Group, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:286IGBN6 2405685:GAPR3LZN
Keywords: ___working_potential_duplicate

Exploring the fundamental factors of digital inequality in Bangladesh - Islam, Muhammad Nazrul; Inan, Toki Tahmid (SAGE Open, 2021)
KerkoCite.ItemAlsoKnownAs: 10.1177/21582440211021407 2339240:C3ZIMHJY 2405685:TDV2W3I9

The state of education in urban slums of Bangladesh - Khondoker, Zarine Anan (BRAC Institute of Governance and Development, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:KQ6BMYBH 2405685:BWLXUGA2

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
ZenodoArchiveID: 4706067 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706067 2339240:Y24AUHV8 2405685:I3AV65H3 2405685:WQ8HX957
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Telementoring and homeschooling during school closures: A randomized experiment in rural Bangladesh - Hassan, Hashibul; Islam, Asad; Siddique, Abu; Wang, Liang Choon (Centre for Development Economics and Sustainability, 2021)
Prolonged school closures due to political unrests, teacher strikes, natural disasters, and public health crises can be detrimental to student learning in developing countries. Using a randomized controlled experiment in 200 Bangladeshi villages, we evaluate the impact of over-the-phone mentoring and homeschooling support delivered by volunteers on the learning outcomes of primary school children during school closures caused by the coronavirus pandemic. The telementoring program improved the learning outcomes of treated children by 0.75 SD and increased homeschooling involvement of treated mothers by 0.64 SD. The impacts on learning are driven primarily by the direct mentoring of children and to some extent also by the increased homeschooling involvement of mothers. Academically weaker children and households from relatively lower socioeconomic backgrounds benefitted the most from telementoring. These findings suggest that learning crises in low-resource settings can be addressed by simple and very low-cost technology solutions.
KerkoCite.ItemAlsoKnownAs: 2339240:5YSHGI3S 2339240:7WBML8RC 2405685:6J9MZIZY 2405685:XE45G75X 2405685:XU7PCDNA 2534379:RF4FNWBS
Keywords: ___working_potential_duplicate

Telementoring and homeschooling during school closures: A randomized experiment in rural Bangladesh - Hassan, Hashibul; Islam, Asad; Siddique, Abu; Wang, Liang Choon (SocArXiv, 2022)
Using a randomized controlled experiment in 200 Bangladeshi villages, we evaluate the impact of over-the-phone mentoring and homeschooling support delivered by volunteers on the learning outcomes of primary school children during school closures caused by the coronavirus pandemic. The telementoring program improved the learning outcomes of treated children by 0.75 SD and increased homeschooling involvement of treated mothers by 0.64 SD. The impacts on learning are driven primarily by the direct mentoring of children and to some extent also by the increased homeschooling involvement of mothers. Academically weaker children and households from lower socioeconomic backgrounds benefitted the most from telementoring.
KerkoCite.ItemAlsoKnownAs: 10.31235/osf.io/mhyq5 2339240:9PH6DMPD 2405685:PADF6IYS

Telementoring and homeschooling during school closures: A randomized experiment in rural Bangladesh - Hassan, Hashibul; Islam, Asad; Siddique, Abu; Wang, Liang Choon (SocArXiv, 2022)
Using a randomized controlled experiment in 200 Bangladeshi villages, we evaluate the impact of over-the-phone mentoring and homeschooling support delivered by volunteers on the learning outcomes of primary school children during school closures caused by the coronavirus pandemic. The telementoring program improved the learning outcomes of treated children by 0.75 SD and increased homeschooling involvement of treated mothers by 0.64 SD. The impacts on learning are driven primarily by the direct mentoring of children and to some extent also by the increased homeschooling involvement of mothers. Academically weaker children and households from lower socioeconomic backgrounds benefitted the most from telementoring.
KerkoCite.ItemAlsoKnownAs: 10.31235/osf.io/mhyq5 2339240:9PH6DMPD 2405685:PADF6IYS

Telementoring and homeschooling during school closures: A randomized experiment in rural Bangladesh - Hassan, Hashibul; Islam, Asad; Siddique, Abu; Wang, Liang Choon (SocArXiv, 2022)
Using a randomized controlled experiment in 200 Bangladeshi villages, we evaluate the impact of over-the-phone mentoring and homeschooling support delivered by volunteers on the learning outcomes of primary school children during school closures caused by the coronavirus pandemic. The telementoring program improved the learning outcomes of treated children by 0.75 SD and increased homeschooling involvement of treated mothers by 0.64 SD. The impacts on learning are driven primarily by the direct mentoring of children and to some extent also by the increased homeschooling involvement of mothers. Academically weaker children and households from lower socioeconomic backgrounds benefitted the most from telementoring.
KerkoCite.ItemAlsoKnownAs: 10.31235/osf.io/mhyq5 2339240:9PH6DMPD 2405685:PADF6IYS

Summative Evaluation of GPE’s Country-Level Support to Education: Bangladesh - Universalia (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Z5GUHIPP 2405685:BJ22GNWE 4656463:3BTPTHP9

Education sector plan (ESP) for Bangladesh Fiscal years 2020/21-2024/25 - Ministry of Education (Ministry of Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:WE7ZPX8W 2405685:WRBA628Y

Education Sector Plan (ESP) for Bangladesh Fiscal Years 2020/21-2024/25 - MoE (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:XHUT23N9 2405685:MWK38D4Z

COVID 19, Technology-based Education and Disability: The case of Bangladesh - UNESCO (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5B34JWFZ 2405685:7K7JA456

EdTech, Learning and Equity: The EdTech Hub Research Portfolio - Haßler, Björn; Wagner, Dan; Outhwaite, Laura (EdTechHub, 2023)
ZenodoArchiveID: 10079721 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1000 ZenodoArchiveConcept: 10079720
Keywords: _internal; _r:AddedByMyEducationEvidence

Overview of emerging country-level response to providing educational continuity under COVID-19: What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate (2020)
ZenodoArchiveID: 4706062 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706062 2339240:IB8GIAAB 2339240:VEARRJJL 2339240:XRVLW2AX 2405685:BR48DF69 2405685:IPAT355N 2405685:SDTIZDHS
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Creditor Reporting System (CRS) - OECD (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GKAXYNKY 2405685:QF9A6M5Z
Keywords: ___working_potential_duplicate

Revisiting the impact of covid-19 on adolescents in urban slums in Dhaka, Bangladesh: round 2 - Raha, Samira Ahmed; Rana, Sajib; Mamun, Saklain Al; Anik, Mehedi Hasan; Roy, Prantik; Alam, Farhana; Sultan, Maheen (Gender and Adolescence: Global Evidence, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WYUAE2BS 2405685:Y2LGTIPF
Keywords: ⛔ No DOI found

Understanding the first and second digital divides in rural Bangladesh: internet access, online skills, and usage - Siddiquee, Muhammad Shahadat Hossain; Islam, Md. Saiful (BRAC Institute of Governance and Development (BIGD), 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:H7E4MIUY 2405685:82R7AZNN

Toward a holistic approach to EdTech effectiveness: Lessons from Covid-19 research in Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone - Nicolai, Susan; Jordan, Katy; Adam, Taskeen; Kaye, Tom; Myers, Christina (International Journal of Educational Development, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2023.102841 2405685:EFV98PTB

Human Development Reports - United Nations Development Programme (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:AD2VSI2P 2405685:KA8YNP9D

OU part of £5.5m research portfolio to improve education tech in low and middle income countries - Grimette, Hannah (OU News, 2022)
The Open University (OU) has launched a study with global research partner, Edtech Hub, to investigate the impact of technology on teaching in Bangladesh. Part of EdTech's first research portfolio, the OU's 3Mpower is one of 13 projects, which represents the largest investment in primary research on EdTech's use in low- and middle-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:M5XGVS2H 2405685:EXXQ3R4B

How many children and young people have internet access at home - UNICEF; ITU (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:T2EURV3P 2405685:E3JV6NQZ

Reopening Schools - When and how - Campe (Evernote, 2021)
Timing of the survey - The survey was conducted between 7 to 22 November 2020. Slide 9 - % students who participated in distance learning in the last 2 weeks prior to the survey Primary - 31.4% Second...
KerkoCite.ItemAlsoKnownAs: 2339240:3PDAXZPR 2405685:MUJGM6QH

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7310489 ZenodoArchiveConcept: 7310488 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7310489 10.53832/edtechhub.0133 2405685:NP52QFM8
Keywords: _r:AddedByZotZen

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Inclusion and education: all means all - UNESCO (UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:CHMAUW76 2405685:EX9FXZIX

Guidance Note 8 Resilient and sustainable energy solutions From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684327 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684327 2339240:J6VCPUDV 2405685:57FXZ5EA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance on Distance Learning Modalities to Reach All Children and Youth During School Closures - UNICEF Regional Office for South Asia (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:29QHBJD5 2405685:4TXJ8GQB

Guidance on Distance Learning Modalities to Reach All Children and Youth During School Closures - UNICEF Regional Office for South Asia (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:29QHBJD5 2405685:4TXJ8GQB

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2405685:JPXVGB3A 2405685:MNMTIMGA
Keywords: _r:AddedByZotZen

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
ZenodoArchiveID: 4556925 PreviousDOI: 10.5281/zenodo.3948175 PreviousDOI: 10.5281/zenodo.4477170 PreviousShortDOI: 10/gg7sp2 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948175 10.5281/zenodo.3948174 10.5281/zenodo.3948175 10.5281/zenodo.4477170 10.5281/zenodo.4556925 2339240:6NYL4Q6K 2339240:782897NS 2339240:CQIWZXYK 2339240:FFVXKB6Y 2339240:FH2WAXTQ 2339240:KAWEDEAZ 2339240:L9THHN3N 2339240:P8B4HPZC 2339240:QLA593HB 2339240:T58E6LDA 2339240:T8L6PTRX 2339240:VZBB4HAF 2405685:839AFBBS 2405685:89H7NAA7 2405685:A2II5ZV7 2405685:A49KTEL6 2405685:AT6JS3QN 2405685:CJR7PMKJ 2405685:DEXS2WA8 2405685:FFSBB3JJ 2405685:NQSPAG3I 2405685:RVZFVD7G 2405685:U95XV67E 2405685:WJRBJQBN 2534378:8FA5G2KF
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, , Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4917252 10.5281/zenodo.4917252 2339240:G2X4SJI9 2339240:MUSPGK9F 2339240:MVU3QIHM 2339240:NQF22P32 2405685:B2ABXUCR 2405685:D6PWMC4I 2405685:HW7NU96L 2405685:JWIHBL5M 2405685:PXBXCZ29 2405685:YHC5ZPU8
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

The latent digital divide and its drivers in e-learning among Bangladeshi students during the COVID-19 pandemic - Badiuzzaman, Md; Rafiquzzaman, Md; Rabby, Md Insiat Islam; Rahman, Mohammad Mustaneer (Information, 2021)
The devastating COVID-19 pandemic forced academia to go virtual. Educational institutions around the world have stressed online learning programs in the aftermath of the pandemic. However, because of insufficient access to Information Communication Technology (ICT), a substantial number of students failed to harness the opportunity of online learning. This study explores the latent digital divide exhibited during the COVID-19 pandemic while online learning activities are emphasised among students of Bangladesh. It also investigates the digital divide exposure and the significant underlying drivers of the divide. In order to accomplish this, a cross-sectional survey was employed to collect quantitative data, mixed with open-ended questions were utilised to gather qualitative information from the student community. The findings revealed that despite the majority of students having physical access to ICT, only 32.5% of students could attend online classes seamlessly. In total, 34.1% reported data prices as the critical barrier, while 39.8% identified poor network infrastructure as the significant barrier preventing them from participating in online learning activities. Although most students possess physical access to various devices and the Internet, they face the first-level digital divide due to the quality of access and price of cellular Internet. Consequently, they fail to take advantage of physical access, resulting in the third-level digital divide (utility gap), which submerges them into a digital divide cycle. The primary objective of this study is to explore the underlying issues of the digital divide among Bangladeshi students. This will assist relevant stakeholders (e.g., the Bangladesh government, educational institutions, and researchers) to gain necessary insights and theoretical understanding of underlying limitations and emergent directions to arrange adequate support for underprivileged students to undertake essential online learning activities.
Number: 8 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/info12080287 2339240:6S36DZH9 2405685:BTG5QS57
Keywords: COVID-19; digital divide; multi-level digital divide; online learning

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
ZenodoArchiveID: 4556935 PreviousDOI: 10.5281/zenodo.4476991 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3956366 10.5281/zenodo.3956366 10.5281/zenodo.4476991 10.5281/zenodo.4556935 2259720:BFY7A76P 2339240:3WZUWHB3 2339240:CVI8639W 2339240:G8MSWBJC 2339240:IF3IMDSW 2339240:NUYRVP8T 2339240:UXMEFECL 2405685:BVXSZ7G4 2405685:BZFLWXG6 2405685:DPRU64AB 2405685:FMULV6ZI 2405685:TJ95P4G4 2405685:UJF6X47J 2405685:UVB294JN 2405685:Y3XDX8FW 4803016:WC4XVPPN
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7245945 ZenodoArchiveConcept: 7245944 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7245945 10.53832/edtechhub.0128 2405685:X8MUXS39
Keywords: _r:AddedByZotZen

Assessing the real-life socio-economic scenario of established slums in Dhaka: the cases of Korail and Sattola - Bashar, Raisa; Tonmoy, Sirajus; Ria, Alvira; Khan, Nazmul (European Online Journal of Natural and Social Sciences, 2020)
The research aims to assess the current situation of three primary socioeconomic indicators, namely education, health and water availability at the two most established slums of Bangladesh's capital Dhaka-Korail and Sattola. Surveys, using cluster and then random sampling to target households, and analysis, found that both slums' children's education level was moderate with 52%-68% and 20%-28% availing primary and secondary education, respectively; several NGOs had helped to establish brick-and-mortar latrines and disseminate necessary and effective awareness about sanitation; and surveyed slum dwellers were economically strong, with 68%-70% of the interviewed households' income levels being 10,000-15,000 BDT (USD 118-178) per month. A comparative analysis with national level statistics also yielded that the conditions in these slums are truly better than previously thought. Primary recommendation includes in-depth monitoring to understand why such large numbers live in slums, even though they can afford better.
KerkoCite.ItemAlsoKnownAs: 2405685:Y4FHHY92
Keywords: ⚠️ Invalid DOI

Educational Technology in Developing Countries: A Systematic Review - Rodriguez-Segura, Daniel (University of Virginia, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:3NFUQ2N5 2339240:7X8NJI23 2339240:AAP9R7UD 2339240:TY3PYSTX 2405685:5IRBQ464 2405685:5J25FLQT 2405685:RQ4ND4UQ 2405685:RVLBVG3I 2405685:YLEQ3IT6
Keywords: ___working_potential_duplicate

Lowering Barriers to Remote Education: Experimental Impacts on Parental Responses and Learning - Beam, Emily; Mukherjee, Priya; Navarro-Sola, Laia (SSRN Electronic Journal, 2022)
We conduct a randomized controlled trial with households of secondary school students in Bangladesh to investigate how parents adjust their investments in response to three educational interventions: an informational campaign about an educational phone application, an internet data subsidy, and oneon-one phone learning support. We find that offering an educational service in a context where other barriers to take-up exist can still trigger parental educational investments by acting as a signal or nudge. These behavioral changes result in lasting learning gains concentrated among richer households, reflecting that the relevant behavior change—increased tutoring investment—is easier for them to implement. In contrast, when interventions do increase take-up, they have the potential to narrow the socioeconomic achievement gap. We observe that increased usage of the targeted educational service limits parental behavioral responses. This implies that learning gains in these cases are directly caused by the potential effectiveness of the services adopted. In our setting, remote one-to-one teacher support improves learning among students from poorer households, whereas receiving the free data package jointly with the app information has no impact on learning.
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4234910 2339240:Y3YD9HTV 2405685:YFMSGQUG

Digital Divide or Digital Provide? Technology, Time Use, and Learning Loss during COVID-19 - Asadullah, M. Niaz; Bhattacharjee, Anindita (The Journal of Development Studies, 2022)
COVID-19 school closure has caused a worldwide shift towards technology-aided home schooling. Given widespread poverty in developing countries, this has raised concerns over new forms of learning inequalities. Using nationwide data on primary and secondary school children in slum and rural households in Bangladesh, we examine how learning time at home during the early months of school closure varies by access to technology at home. Data confirms a significant socio-economic and gender divide in access to TV, smartphone, computer, and internet among rural households. However, the analysis of daily time use data shows only a modest return to a technology in terms of boosting learning time at home. The learning-grade gradient is shallow and insensitive to TV, smartphone, and computer access at home. We also find no evidence that technology access per se helps learning by boosting time spent in online schooling and private supplementary coaching/tutoring. While technology access matters in households where parents act as home tutors, the magnitude of such a complementary effect are not large. The results imply a loss of out-of-school learning time during school closure even in households with technology access. We consider additional hypotheses relating to institutional and socio-economic barriers to home-based learning in developing countries.
Publisher: Routledge _eprint: https://doi.org/10.1080/00220388.2022.2094253 KerkoCite.ItemAlsoKnownAs: 10.1080/00220388.2022.2094253 2405685:4QFIBL3G
Keywords: COVID-19; D10; I21; J22; Q50; home-based education; learning crisis; school closure

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341466 ZenodoArchiveConcept: 7341465 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341466 10.53832/edtechhub.0137 2405685:VVT2BI9M
Keywords: _r:AddedByZotZen

Learning continuity in response to climate emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6
Keywords: _r:AddedByZotZen

Adolescent problematic internet use and parental mediation: A Bangladeshi structured interview study - Chandrima, Rubaiya Matin; Kircaburun, Kagan; Kabir, Humyon; Riaz, Baizid Khoorshid; Kuss, Daria J.; Griffiths, Mark D.; Mamun, Mohammed A. (Addictive Behaviors Reports, 2020)
Internet-related problems such as excessive internet use, problematic internet use (PIU), and internet addiction, are becoming increasingly studied among Bangladeshi adult students, but there has been little research among adolescents. In Bangladesh, there has been no research examining the role of parental mediation in their children's internet use. Therefore, the present structured interview study investigated Bangladeshi adolescent PIU and its associated socio-demographics, internet use behaviors, and the parental mediation role among 350 high school students residing in Dhaka. The results showed that 84 of adolescents (24.0%) were classified as having PIU (cut-off score of ≥ 50 on the Internet Addiction Test) and nine adolescents (2.6%) were classified as having a severe dependency on the internet (cut-off score of >80 on the Internet Addiction Test). According to hierarchical regression analysis, significant PIU correlates included lower academic results, both parents' lower education, mother working outside the home, more than four days' weekly internet use, more than two hours daily internet use, and active mediation. Additionally, internet use behaviors (i.e., internet use locations, devices, purposes, and applications) and parental internet mediation dimensions other than active mediation (i.e., restrictive mediation, active mediation internet safety, monitoring, and technical mediation) were significantly related to PIU in t-tests and correlation analysis respectively. However, they were non-significant in the hierarchical regression analysis when included into equation altogether. The present study's findings will be helpful in developing country-level policymaking decisions and facilitating future research in the country.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.abrep.2020.100288 2339240:JINXJ99U 2405685:39YEHSPC
Keywords: Bangladeshi adolescence; Internet addiction; Internet use behaviors; Parental mediation; Problematic internet use

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Education and Covid-19 response: bringing schools and learning back on track - Ahmed, Manzoor; Rahaman, Mostafizur; Hossain, Syed Shahadat; Ahmed, Ghiasuddin (Education Watch/Campaign for Popular Education (CAMPE), 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:G9RHE7L5 2405685:7U3LNXWS

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
ZenodoArchiveID: 5652169 previousZenodoArchiveID: 3805843 previousshortDOI: 10/gg7sqk previousDOI: 10.5281/zenodo.3805843 EdTechHub.Copy: 2129771:DQLDNQGU shortDOI: 10/gg7sqk KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3805843 10.5281/zenodo.3805843 10.53832/edtechhub.0023 10/gg7sqk 2129771:DQLDNQGU 2339240:IWW8CJZN 2339240:N5RG3WT2 2339240:QGMNZZER 2405685:53YEZE6A 2405685:933PQ5Q6 2405685:MHEB7LKZ 2405685:WBNK52L7
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Learning continuity in response to climate emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2405685:FKCF86HV 2405685:IHTU7JRT
Keywords: _r:AddedByZotZen

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7371460 ZenodoArchiveConcept: 7371459 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7371460 10.5281/zenodo.7473922 10.5281/zenodo.7500121 10.53832/edtechhub.0151 2339240:BE2J66WG 2405685:BBAPFKW4 2405685:JHWKC6F4 2405685:P833K7KC 2405685:YLS6YQ3U
Keywords: _r:AddedByZotZen

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
ZenodoArchiveID: 4737460 previousDOI: 10.5281/zenodo.4556939 PreviousDOI: 10.5281/zenodo.3958002 PreviousDOI: 10.5281/zenodo.4477168 PreviousShortDOI: 10/ghgnfc Publisher: Zenodo Version Number: 1 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3958002 10.5281/zenodo.3958002 10.5281/zenodo.4477168 10.5281/zenodo.4556939 10.5281/zenodo.4737460 2259720:36F6CWBU 2339240:23GW5XQ8 2339240:6YJ555Q6 2339240:9CAC5BI5 2339240:ABKFKG4Q 2339240:FC5RCEYW 2339240:GCYWZ39Q 2339240:GZYWFIHI 2339240:L326GM9E 2339240:MQ8QSK5B 2339240:PB295ID7 2339240:Q8QJYXRQ 2339240:TIVTGHAA 2339240:TYYDMDPR 2339240:VFBZXUEM 2339240:VFBZXUEM; 2339240:WVUDHTHF 2405685:4XTHDWDA 2405685:6PE7ANUL 2405685:78VECZYK 2405685:ALEXQL2P 2405685:BLT5KKXG 2405685:C4JLZV3D 2405685:CZBRW85R 2405685:E4TFYPYP 2405685:IV7MEXRW 2405685:NMXFFTIB 2405685:PKS7U5LC 2405685:RTIHY6H8 2405685:SA26Q7UG 2405685:V7VESTKX 2405685:WR37F768 2405685:YHERHZKV 2405685:YNMUHK9S 2534378:5794CXFP 2534378:5GTJL9K7
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Hasiniavo. Rasolohery (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6475261 10.53832/edtechhub.0090 2405685:DSG9QF4F 2405685:GBQT3KMA
Keywords: _r:AddedByZotZen

COVID-19 response and recovery plan: education sector - Ministry of Primary and Mass Education (Ministry of Education, Government of the People’s Republic of Bangladesh, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5R6MZFGM 2405685:2GTFI3D5

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen

Key considerations when developing an ICT in Education strategy - AlSheikhTheeb, Thaer; Chuang, Rachel; Pandit, Sanjana (EdTech Hub, 2022)
This report was commissioned by UNICEF and produced under UNICEF and EdTech Hub’s global partnership, in response to a request from the UNICEF Laos team that was submitted to the EdTech Hub Helpdesk. It presents key considerations on the overarching process to develop an ICT in Education strategy (e.g., components, stakeholders, timelines) and lists examples of other national ICT in Education and EdTech strategies. Keywords: EdTech strategies; ICT in Education strategies An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6676586 10.53832/edtechhub.00100 10.53832/edtechhub.0100 2405685:2XS75XAU
Keywords: _r:AddedByZotZen

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4596486 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4596486 2129771:3CUB9UK6 2339240:3JHAWKKZ 2339240:NHJQTPKC 2339240:R2MHQ7R6 2405685:BTQ4CU7R 2405685:NZUHTJBG 2405685:R4LUIDP5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4633326 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4633326 2339240:DNCQ88UV 2339240:ILPGZU8E 2339240:SGQPIKMM 2405685:AR7EAIDU 2405685:XBPZPS3P 2405685:ZL7H9N8P
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:T7BK22I4

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4617798 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4617798 2339240:V3PGSF2W 2405685:EH6F8M5P
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2405685:4CB23ZC6 2405685:AG764A26
Keywords: _r:AddedByZotZen

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
ZenodoArchiveID: 5652129 previousZenodoArchiveID: 3891379 previousshortDOI: 10/ghgnfv previousDOI: 10.5281/zenodo.3891379 EdTechHub.Source: 2405685:LP4PGMNA shortDOI: 10/ghgnfv KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3891379 10.5281/zenodo.3891379 10.5281/zenodo.4348995 10.53832/edtechhub.0043 10/ghgnfv 2129771:3YH4WC8N 2129771:J35ZR45N 2339240:6VEXVUL7 2339240:CDU93LQU 2339240:CUSR6ZBJ 2339240:FS3CFIBL 2339240:N7RDGZGY 2339240:V229A7WT 2339240:Z4FHRC9L 2405685:4PAZ4ZQH 2405685:8WYASBE4 2405685:KL56SD42 2405685:LP4PGMNA 2405685:S2A2EQQC 2405685:WFMBLBBE 2405685:XIQ5CL9B 2405685:XJ42VUQG 2405685:YY4LI6EI
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (Education Commission, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
shortDOI: 10/ghgk64 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3983877 10/ghgk64 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:7SUZMICK 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:88MADQ2R 2405685:FPPVW2ZG 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6 2405685:WVC3S4C8
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
shortDOI: 10/ghgk63 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4118177 10/ghgk63 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:FTULJL3H 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:2G7TFTEB 2405685:F2B8T3ZP 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
previousshortDOI: 10/ghgnf6 previousshortDOI: 10/ghgnf6 previousDOI: 10.5281/zenodo.3406132 previousshortDOI: 10/ghgnf6 EdTechHub.Source: 2405685:KWJRW62J EdTechHub.Source: <this> shortDOI: 10/ghgnf6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3406132 10.5281/zenodo.3406132EdTechHub.ItemAlsoKnownAs: 10.53832/edtechhub.0010 10/ghgnf6 2129771:3H8JIJ9T 2129771:MG4TM5B3 2339240:CN8LY32H 2339240:EG4V9NYX 2339240:T37Q6QE6 2339240:W2B4DTPS 2405685:7EP4VHD7 2405685:B76WDWTE 2405685:KWJRW62J 2405685:QFMSIUXQ 2405685:Y4EVL7PR 2486141:TAPS8LVP
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
ZenodoArchiveID: 4684361 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684361 2339240:SL23268I 2339240:VTWI3GZJ 2405685:UF3XJXGS 2405685:UXHEIEWM 2405685:ZA9RWW28
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2405685:V8CZHW5B
Keywords: _r:AddedByZotZen

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, , Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5120788 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5120788 10.5281/zenodo.5142473 2405685:3C8VWLJP 2405685:772S7Z4R 2405685:CW2FHVT8
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2405685:2437EGZU
Keywords: _r:AddedByZotZen

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2405685:BBQE9QUM 2405685:UUDK52LQ

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Child-directed Tablet-based Learning: Project Launch, Monitoring, and Improvement Toolkit - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MJ592UKH

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
2339240:7FA4YDWJ 2339240:YBKKN8XE KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5498054 10.5281/zenodo.5498054 2339240:3H4M8YJ8 2339240:5S4BZY48 2339240:SRWI5WQJ 2405685:BCFK4Q23 2405685:JR65CZU2 2405685:JTKTA5X5 2405685:VQ3F9NQ7 2405685:ZLATZSGU 4656463:RIFY2UNL
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PNMXVDQ2 2405685:A4NNJNSJ 2405685:GBIY52AG

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2405685:HEXCEXFK 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen

Problem Analysis and Focus of EdTech Hub’s Work: Technology in Education in Low- and Middle-Income Countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (The EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:322MPSF7 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:WEEFFITS 2405685:347U73VH 2405685:8F46F44X 2405685:94F2MYRK 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH